2020
DOI: 10.3390/s20133659
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution Analysis on Hyperspectral Corn Leaf Images for Improved Phenotyping Quality

Abstract: High-throughput imaging technologies have been developing rapidly for agricultural plant phenotyping purposes. With most of the current crop plant image processing algorithms, the plant canopy pixels are segmented from the images, and the averaged spectrum across the whole canopy is calculated in order to predict the plant’s physiological features. However, the nutrients and stress levels vary significantly across the canopy. For example, it is common to have several times of difference among Soil Plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The major source of error is the individual differences between each soybean canopy. As the soybeans are grown in the greenhouse, the microclimate will have effect on the growing of the canopy that could induce large variance to plant grow [ 25 ]. Another source of error is induced when inpainting the images as a small portion of the images are not the original leaf tissue.…”
Section: Validation Results Of the Capability Of Separating Nitrogen ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The major source of error is the individual differences between each soybean canopy. As the soybeans are grown in the greenhouse, the microclimate will have effect on the growing of the canopy that could induce large variance to plant grow [ 25 ]. Another source of error is induced when inpainting the images as a small portion of the images are not the original leaf tissue.…”
Section: Validation Results Of the Capability Of Separating Nitrogen ...mentioning
confidence: 99%
“…Multiple studies have shown that SPAD readings are correlated with various crop traits [ 21 , 22 , 23 ]. However, since the SPAD meter only measures a small area of the leaf, different locations on the same leaf can yield different results [ 17 , 24 ] Additionally, studies have suggested that color distribution over the entire leaf is a better indicator of stress [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visual monitoring ranges from custom-made devices such as LeafSpec [26,27], the use of a normal camera combined with a microcontroller, a processor board [28][29][30] or a smartphone camera [31][32][33]. Papers propose monitoring plants with different types of cameras: standard spectral camera, infrared camera, thermal imaging camera, or color component camera.…”
Section: Sensorsmentioning
confidence: 99%
“…After data collection, standard imaging processing protocols were performed to extract the interested plant phenotyping features [5,31,32]. The raw hyperspectral images were firstly calibrated with the real-time white reference.…”
Section: Image Segmentation and Feature Extractionmentioning
confidence: 99%